Computer simulation of open-circuit fault-tolerant boost rectifier based on SPMC - Hayroman, Muhammad Hakiem; Baharom, Rahimi; Abdul Munim, Wan Noraishah Wan; Muhammad, Khairul Safuan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This paper presents a computer simulation of an open-circuit fault-tolerant boost rectifier based on a single-phase matrix converter using MATLAB/ Simulink. The proposed converter employs a fault identification technique to identify the faulty switch by generating a binary code extracted from the output voltage, magnitude of inductor current, and cycle of the input power supply. Upon identifying the faulty switch, the current is redirected to any available path through operational switches by controlling the switching devices. The aim is to ensure uninterrupted power supply from the source to the load. The paper includes a detailed analysis of the fault identification technique and the options for rerouting the current path. The outcomes of this paper are simulated using MATLAB/Simulink.